Alcohol and recreational drug use in young adults with type 1 diabetes. (August 2017) - Pastor, Adam; Conn, Jennifer; Teng, Jessie; O'Brien, Casey L.; Loh, Margaret; Collins, Lisa; MacIsaac, Richard; Bonomo, Yvonne
Highlights: Alcohol and drug use amongst young adults with type 1 diabetes is likely similar to the surrounding general population. There is evidence for increased mortality and morbidity for young adults with type 1 diabetes who use alcohol and drugs. Alcohol and drugs have important physiological, behavioural and mental health effects specific to type 1 diabetes. Screening, intervention and harm minimisation advice is likely to reduce morbidity and mortality. Abstract: Alcohol and other recreational drug use reaches peak prevalence in young adulthood, including for those with chronic medical conditions such as type 1 diabetes. This review summarises the current literature on the patterns of substance use amongst young adults with type 1 diabetes and the mechanisms through which alcohol and recreational drugs may affect diabetes related health outcomes. These include the direct physical effect of intoxication, as well as the effects of alcohol and drugs on mental health and glucose metabolism. Evidence for increased associated mortality and morbidity is also presented, and current guidelines, management strategies and directions for further research are discussed.